A novel variation of the suture suspension facelift. (10th February 2020) - Ugradar, Shoaib; Isse, Nicanor; Goldberg, Robert A.; Fodor, Peter
Abstract: Background: We propose a technical variation of the minimally invasive suture suspension facelift. Methods: A novel variation of the minimally invasive facelift is proposed. The technique consists of two components. The anterior component addresses aging of the midface by anchoring the SMAS on to the sturdy retroauricular supra‐helical deep temporal fascia using approximately 6‐8 passes of a 4/0 Mersilene suture. The posterior component addresses cervical aging by securing the posterior edge of the platysma onto the sturdy mastoid fascia, using multiple loops of a 4/0 Mersilene suture. This technique was performed on 100 consecutive patients between 2005 and 2010. Results: The technique was found to be safe due to the plane of dissection remaining superficial to the parotid gland in the anterior component. There were no instances of facial nerve injury or sensory disturbance. None of the patients required a secondary procedure within the first 18 months following the procedure. Conclusions: This technique offers a safe and effective option for patients who seek a facelift, especially in combination with other procedures. It is envisaged that the use of multiple loops of suture to anchor mobile tissue onto fixed sturdy fascia will contribute to the longevity of the results. The limited skin undermining also makes this procedure a better choice for smokers.